Penggunaan Web Scraping dalam Mengetahui Jangkauan Pelayanan Fasilitas Pendidikan di Kabupaten Jember - Adhitya Ferdiansyah Murdiyanto (MATRAPOLIS: Jurnal Perencanaan Wilayah dan Kota, 2023)
The population growth in Jember Regency which increases every year causes the need for educational facilities. In a period of 21 years, the population of Jember Regency has increased by 13.76%. Based on the Central Statistics Agency, the average length of schooling in Jember Regency is still below the average for the Province of East Java. This indicates a problem with the education system in Jember Regency. Another problem is the lack of synchronization between the data on the number of educational facilities and the data on educational locations. Big data analysis is one of the solutions to overcome this. One analysis that can be easily developed is web scraping. Where in the use of web scraping it provides features that are easy to use by all groups. In this study, researchers used web-scraping to collect data on the number of educational facilities and to analyze the radius of education services in Jember Regency. The web-scraping results show that the total number of educational facilities in the district is 665 units. There are 289 SD facilities, 277 SMP facilities and 127 SMA facilities. The nearest neighbor analysis results obtained a value of 0.562 which is included in the grouped classification. From the results of the service radius, 95.54% of educational facilities have served settlements and 4.46% have not been served by educational facilities